Effect of IL-8, IL-2 and IL-15 Gene Expression in Different Tissues of Jinghai Yellow Chicken Infected by Eimeria Tenella. (September 2020) - Wang, Chengli; Yu, Hailiang; Wang, Xiaohui; Zou, Wenbin; Mi, Changhao; Hu, Tingyan; Dai, Guojun
Abstract: For research the role of IL-8, IL-2 and IL-15 genes in immune regulation after E. tenella infection, with Jinghai yellow chickens as material, the mRNA expression levels of IL-8, IL-2 and IL-15 genes in ten different tissues after infection with different doses of E. tenella oocysts were compared to determine the expression difference of the three genes in the same tissue with different infection doses. The results showed that IL-8, IL-2 and IL-15 genes were expressed in all tissues at the 7th day of infection, and the infection group was higher than the control group in most tissues. The mRNA expression of IL-8 gene in infection group II in the liver was significantly higher than that in the other two groups ( P <0.05), and was extremely far higher the other two groups in the spleen and cecum (P <0.01 ). The mRNA expression of IL-8 gene in infection group II was also far higher in the bursa and thymus than that in the control group (P <0 .05). The mRNA expression of IL-2 gene in infection group II in liver and lungs were significantly (P <0 .05) and extremely significant (P <0.01 ) higher than that in the control group, respectively. The IL-15 gene mRNA expression. The infection group was obvious (P <0 .05) and extremely significantly (P <0.01 ) higher in the lung and cecum than that in the control group, respectively. These results indicate that the three genes play a role in the infection of E. tenella in chickens, and provide a basis for the subsequent study of the relationship between these three genes and chicken coccidiosis resistance.